WS2-Graphite Dual-Ion Batteries - Bellani, Sebastiano; Wang, Faxing; Longoni, Gianluca; Najafi, Leyla; Oropesa-Nunez, Reinier; Castillo, Antonio E. Del Rio; Prato, Mirko; Zhuang, Xiaodong; Pellegrini, Vittorio; Feng, Xinliang; Bonaccorso, Francesco (Nano Letters, 2018)
A novel WS2-graphite dual-ion battery (DIB) is developed by combining a conventional graphite cathode and a high-capacity few-layer WS2-flake anode. The WS2 flakes are produced by exploiting wet-jet milling (WJM) exfoliation, which allows large-scale and free-material loss production (i.e., volume up to 8 L h-1 at concentration of 10 g L-1 and exfoliation yield of 100%) of few-layer WS2 flakes in dispersion. The WS2 anodes enable DIBs, based on hexafluorophosphate (PF6 -) and lithium (Li+) ions, to achieve charge-specific capacities of 457, 438, 421, 403, 295, and 169 mAh g-1 at current rates of 0.1, 0.2, 0.3, 0.4, 0.8, and 1.0 A g-1, respectively, outperforming conventional DIBs. The WS2-based DIBs operate in the 0 to 4 V cell voltage range, thus extending the operating voltage window of conventional WS2-based Li-ion batteries (LIBs). These results demonstrate a new route toward the exploitation of WS2, and possibly other transition-metal dichalcogenides, for the development of next-generation energy-storage devices.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Dual-ion batteries; electrical energy storage (EES); transition metal dichalcogenides (TMDs); tungsten disulfide (WS; two-dimensional materials; wet-jet milling exfoliation